1998
DOI: 10.1590/s0074-02761998000200007
|View full text |Cite
|
Sign up to set email alerts
|

Metazoan Parasite Infracommunities in Five Sciaenids from the Central Peruvian Coast

Abstract: Key words: marine sciaenids -parasite community -diversity -Peruvian coastThe structure of the metazoan parasite community of fish, like that of other vertebrates and invertebrates, has recently attracted some attention. The first definition of a parasitic community was given by Cloutman (1975) who said that it is "the complex of individuals belonging to the different parasite species inhabiting a host". Studies focusing on the structure of parasite communities in marine fish, in terms of diversity, are scarce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
18

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 19 publications
1
24
0
18
Order By: Relevance
“…The parasite success in the deep sea is directly related to the abundance and diversity of hosts in the benthic community (Campbell et al 1980, Oliva & Luque 1998, therefore, the parasite richness is correlated with the diversity of free-living fauna in a certain area (Poulin 1995). The narrowness of the continental shelf in this geographical area has also been considered as an important abiotic factor that explains this phenomenon (Oliva 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The parasite success in the deep sea is directly related to the abundance and diversity of hosts in the benthic community (Campbell et al 1980, Oliva & Luque 1998, therefore, the parasite richness is correlated with the diversity of free-living fauna in a certain area (Poulin 1995). The narrowness of the continental shelf in this geographical area has also been considered as an important abiotic factor that explains this phenomenon (Oliva 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This must be true for those studies that imply samples for only one geographical locality independent of the host latitudinal range (i.e. Oliva, 1994;Gonzalez & Acuña, 1998;Oliva & Luque, 1998). In this paper, is demonstrated that the poor fauna of adult intestinal endohelminth parasites of the jack mackerel remains along more than 30° of latitudinal gradient.…”
Section: O F the Listed Species Inmentioning
confidence: 67%
“…A characteristic of marine fishes from Chile and Perú is the sparse of their parasite fauna (metazoa), when compared with related fishes from different geographical areas; this phenomena has been documented for the flatfish Paralichthys adpersus by Oliva et al (1996), the rock fish Sebastes capensis by Gonzalez & Acuña (1998) Luque (1998). In the main, differences are related to trophically transmitted parasites, specifically digeneans.…”
Section: O F the Listed Species Inmentioning
confidence: 98%
See 2 more Smart Citations